NEGOTIATING PIETY AND PROFESSIONALISM: Hadith, Patriarchy, and the Digital Contestation of Muslimah’s Roles in Islamic Fashion - Hadiana, Shinta Nuriyah; Rochmawati, Ida; Ilmiyah, Dakhirotul; Fahimah, Rifiyatul (UIN Sunan Kudus, 2025)
This article analyzes the negotiation between piety and professionalism in the discourse rejecting Muslimah (Muslim women) as models for Islamic fashion on social media. This study employs a qualitative netnographic approach, utilizing the Mubādalah (reciprocal or mutual) framework to analyze digital content from the Instagram account @raehanul_bahraen, specifically related to religious narratives on women and modesty. The findings indicate that hadiths related to modesty, decency, and dress codes are frequently simplified and instrumentalized as moral legitimization tools that tend to reinforce patriarchal structures. However, through Mubādalah hermeneutic analysis, this meaning is reoriented from symbolic prohibition toward reciprocal ethical principles that emphasize shared moral responsibility between men and women. Muslim women’s identities in digital spaces emerge as active agents who negotiate piety, autonomy, and self-expression within the dynamics of religious commodification and algorithmic governance. The integration of netnography and Mubādalah highlights the importance of contextual and inclusive reinterpretation of hadith, fostering a more participatory, ethical, and just understanding of Islam within the contemporary digital religious landscape.